Physical and Chemical Prosperities Difference Between Pulverized Coal Boiler Fly Ash and Circulating Fluidized Bed Combustion Ash - Chen, C.; Li, Q.; Tao, D.J.; Zhai, J.P.; Tao, C.L. (Asian Journal of Chemistry, 2012)
This paper focuses on different prosperities of PC fly ash and CFBC ash. The XRD and SEM/ EDX have been applied. The results show that: CFBC ash contains more CaO and SO3 than PC fly ash while the concentration of SiO2 and Al2O3 is lower. CaO of CFBC ash and C-fly ash concentrate in crystalline phase and amorphous phase separately. The main mineralogy phases of CFBC ash is quartz, anhydrite, calcite, portlandite and albite but no mullite. No spherical microspheres could be observed in CFBC ash by SEM and these micro particles appear porous and irregular. Some crystalline particles including anhydrite and lime could also be found in CFBC ash by SEM.